Experimental analysis on design and implementation of steam oven using copper tubes for heating application. (2022) - Venugopal, D.; Dhanush, R.; Naresh Kumar, K.J.; Jayasankar, T.
Abstract: In this work, an embedded-based approach is used for the Design and Implementation of Steam Oven Using Copper Tubes to maintain the heat of the food at a particular temperature until a given time. Unlike some steam ovens, the steam is generated outside the compartment of our oven, which has many advantages for the heating process: a necessary quantity of steam, maintenance and optimum temperature measurement, time-independent heating durations, and rapid heating on time when it's necessary. This helps us to save time and make the heating process incredibly easy. During the warming process, the steam is allowed to fill the entire oven compartment and boiled water is passed through the copper tubes into the oven compartment at 70 degrees Celsius. This process continues until the desired temperature is reached while retaining its natural flavor when the food is kept open inside the oven chamber.